Case Report: Unmasking a sporadic pediatric tumor emergency: superior vena cava syndrome - Liu, Gui-Liang; Wang, Min; Zhang, Min; Dai, Yan; Zhang, Di-Wen (Frontiers in Pediatrics, 2025)
IntroductionSuperior Vena Cava Syndrome (SVCS) is a rare but serious oncologic emergency in pediatric patients, most commonly caused by mediastinal masses such as lymphomas or leukemias. This condition results from the obstruction of the superior vena cava (SVC), leading to impaired venous return and respiratory and cardiovascular complications, progressive exacerbation in a short period, and an extremely high fatality rate. We report the case of a 12-year-old boy with SVCS caused by a mediastinal mass.Main symptoms/findingsThe patient presented with progressive dyspnea, orthopnea, and swelling of the head and neck. He also exhibited chest tightness, dry cough, and shortness of breath. A chest CT revealed a large anterior mediastinal mass compressing the SVC and main bronchi.Diagnosis, treatment, outcomesThe patient was diagnosed with SVCS secondary to T-cell lymphoblastic lymphoma. Treatment began immediately with oxygen therapy and intravenous dexamethasone to reduce mediastinal compression. Significant clinical improvement was observed within 48 h, with a reduction in dyspnea and swelling. A biopsy confirmed T-cell lymphoblastic lymphoma and multidisciplinary care was pivotal to successful management.ConclusionEarly recognition and treatment of pediatric SVCS are essential to prevent life-threatening complications. Combined with a multidisciplinary approach, corticosteroid therapy was crucial for the patient's rapid recovery. Further research is needed to optimize treatment protocols and improve outcomes for pediatric SVCS cases.